ST Elevation Myocardial Infarction in Young Women Caused by a Coronary Embolism Generated from Mitral Valve Disease: a Case Report - Budi Yuli Setianto; Nahar Taufiq; Muhamad Taufik Ismail (ACI (Acta Cardiologia Indonesiana), 2015)
Coronary emboli causing ST elevation myocardial infarction (STEMI) is a rare condition. Intracardiac thrombus generated by valvular disease is the most common source of intracoronary embolism and mitral stenosis is frequently affected by intraatrial thrombus. Therapeutic strategy of coronary embolism is challenging because there were still no recommendation regarding coronary embolism published to day. We reported A 25 years old woman was admitted to the emergency department because of STEMI with complication of acute pulmonary edema and cardiogenic shock, and recurrent cardiac arrest. Angiographically showed total occlusion of left main artery with thrombotic lesions. Unfortunately after unfractionated heparin (UFH) was given and performed catheter cannulation, thrombus run to distal part of left coconary artery. Procedure is stopped and then patient transferred to cardiac care unit, but death shortly after arrival. Transthroracic echocardiography revealed mild to mild-modertae mitral stenosis with severe regurgitation due to mitral valve prolaps, aortic regurgitation, and left atrial and ventricular dilatation with no thrombus or spontaneous echo contrast, and failed to fi nd thrombus with in atrium. The presence af atrial dilatation and aortic regurgitation increased risk of thrombosis, meanwhile mitral regurgitation were reported as protective factor of atrial thrombosis. The pathophysiology of arterial thrombus or whitethrombus involving platelet activation leads to double antiplatelets and GbIIb/IIIa inhibitior to be more cruciale in coronary embolism. Double antiplatelet dan UFH administration did not improve survival in these patients. So that further research was needed to make a consensus of therapy. Careful assessment of intracardiac thrombus and risk of thromboembolism were important to prevent systemic embolization.Keywords: STEMI, coronary embolism, mitral valve disease.